Optimasi Kinerja Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) Melalui Dialog Kinerja Atasan dan Bawahan - Avanda, Novareza; Said , Moh; Rizki Pratama , Muhammad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
This study aims to investigate the role and optimization of performance dialogue in the performance appraisal process and the preparation of Employee Performance Targets (SKP) in an organizational context. The research methods used were literature study and descriptive analysis. Through the literature study approach, various sources of information relevant to the research topic were identified, including journal articles, books and related documents. The results of the descriptive analysis show that performance dialog has a crucial role in setting performance expectations, developing work plans, and facilitating communication between superiors and subordinates. The practical implication of this finding is the importance of strengthening the performance dialogue process as an integral part of an organization's performance management system. Performance dialogue is also a consideration for superiors in improving policies for individual PPPK employees with efforts to change employee performance goals and in developing effective strategies and policies in managing employee performance and achieving organizational goals efficiently and effectively.